The Checks and Balances Mechanism and the Effectiveness of Parliamentary Oversight as Determinants of the Stability of Presidential Governance - M. Ari Azhari; Yuli Yanti Daaris; Hibby Khoirunnida; Firra Nurfajriah; Lalu Dicky Surya Pandi (Visi Pencerah Nusantara, 2025)
This study aims to analyze the relationship between the checks and balances mechanism, the effectiveness of parliamentary oversight, and the stability of presidential governance through a qualitative approach based on library research and an integrative review method. This approach enables researchers to synthesize various scientific findings from reputable databases, such as Google Scholar, Scispace, DOAJ, and Scopus, to produce a comprehensive conceptual understanding. The results of the study indicate that the checks and balances mechanism operates through two main dimensions: the normative-constitutional one, which defines the boundaries of authority between institutions, and the practical-political one, which influences the effectiveness of oversight implementation. The institutional integrity, deliberative capacity, and public interest orientation of legislators determine the effectiveness of legislative oversight. These findings confirm that the stability of presidential governance is significantly influenced by the synergy between clear institutional design, healthy executive-legislative relations, and the parliament's ability to carry out its oversight function independently. This study recommends a further research agenda regarding the impact of political coalition configurations, multiparty presidentialism, and the digitalization of legislation on optimizing checks and balances in a modern presidential system.